Heavy-mineral analysis and provenance of Yellow River sediments around the China Loess Plateau. (1st September 2016) - Pan, Baotian; Pang, Hongli; Gao, Hongshan; Garzanti, Eduardo; Zou, Yu; Liu, Xiaopeng; Li, Fuqiang; Jia, Yunxia
Highlights: Sediments of the upper and middle reaches of the Yellow River have different heavy mineral assemblages. Compositional changes of sediments in the Inner Mongolia section reflect provenance of arid deserts and seasonal tributaries. The sediments of middle reach reflect the provenance of the Mesozoic sandstones. Abstract: In its upper-middle reaches the Yellow River has high sand contents after traversing through large areas of desert and the China Loess Plateau. Understanding riverbed sediment composition in the channel is critical for the interpretation of the potential provenance, aeolian sand transport and the linkage between the Loess Plateau and the Yellow River. To address these issues, we collected 52 samples from the modern riverbed, proximal deserts, and major tributaries and used analyses of grain size, grain morphology, and heavy-mineral compositions, to establish the spatial distribution and characteristics of source regions and riverbed sediments. The heavy-mineral assemblages demonstrate significant variations for the different sections of the Yellow River. The riverbed samples from the upper reach are dominated by opaque minerals (limonite and magnetite), amphibole and epidote, with minor zircon, tourmaline and rutile. Riverbed sediments from the middle reach are garnet-rich, reflecting the widespread distribution of Mesozoic sandstones. This variability closely reflects the source regions. Our data show that seasonal tributaries (the "Ten Great Gullies") carrying detritus from the Ordos Plateau may account for the localized high garnet concentrations in the Inner Mongolia section of the upper reach. Scanning electron microscope (SEM) imaging of quartz grains show that the river sediments are characterized by composite microtextures acquired in both fluvial and eolian environments of the Hedong, Ulan Buh and Kubuq Deserts. The mineralogical composition in the upper reach (Lanzhou–Yinchuan) is similar to that of sediments in the Loess Plateau and Northeast Tibet Plateau (Western Lanzhou). However, the composition differs markedly from that in the Inner Mongolia section of the upper and middle reaches. This variation indicates that in the upper reach the Northeast Tibet Plateau contributes significant volumes of sediment to the Yellow River and Loess Plateau, but compositions change across the Inner Mongolia section of the upper and middle reaches owing to local sediment supply from arid desert areas and seasonal tributaries.